Binding partner switching on microtubules and Aurora-B in the mitosis to cytokinesis transition - Özlü, Nurhan; Monigatti, Flavio; Renard, Bernhard Y.; Field, Christine M.; Steen, Hanno; Mitchison, Timothy J.; Steen, Judith J. (Molecular & cellular proteomics, 2010)
The cytoskeleton globally reorganizes between mitosis (M phase) and cytokinesis (C phase), which presumably requires extensive regulatory changes. To reveal these changes, we undertook a comparative proteomics analysis of cells tightly drug-synchronized in each phase. We identified 25 proteins that bind selectively to microtubules in C phase and identified several novel binding partners including nucleolar and spindle-associated protein. C phase-selective microtubule binding of many of these proteins depended on activity of Aurora kinases as assayed by treatment with the drug VX680. Aurora-B binding partners switched dramatically between M phase to C phase, and we identified several novel C phase-selective Aurora-B binding partners including PRC1, KIF4, and anaphase-promoting complex/cyclosome. Our approach can be extended to other cellular compartments and cell states, and our data provide the first broad biochemical framework for understanding C phase. Concretely, we report a central role for Aurora-B in regulating the C phase cytoskeleton.